Changes in the Diaphragm Lipid Content after Administration of Streptozotocin and High-Fat Diet Regime - Bartlomiej Lukaszuk; Agnieszka Miklosz; Malgorzata Zendzian-Piotrowska; Beata Wojcik; Jan Gorski; Adrian Chabowski (Journal of Diabetes Research)
The diaphragm is a dome-shaped skeletal muscle indispensable for breathing. Its activity contributes up to 70% of the total ventilatory function at rest. In comparison to other skeletal muscles, it is distinguished by an oxidative phenotype and uninterrupted cyclic contraction pattern. Surprisingly, the research regarding diaphragm diabetic phenotype particularly in the light of lipid-induced insulin resistance is virtually nonexistent. Male Wistar rats were randomly allocated into 3 groups: control, streptozotocin-induced (STZ) type-1 diabetes, and rodents fed with high-fat diet (HFD). Additionally, half of the animals from each group were administered with myriocin, a robust, selective inhibitor of ceramide synthesis and, therefore, a potent agent ameliorating insulin resistance. Diaphragm lipid contents were evaluated using chromatography. Fatty acid transporter expression was determined by Western blot. The STZ and HFD rats had increased concentration of lipids, namely, ceramides (CER) and diacylglycerols (DAG). Interestingly, this coincided with an increased concentration of long-chain (C ≥ 16) saturated fatty acid species present in both the aforementioned lipid fractions. The CER/DAG accumulation was accompanied by an elevated fatty acid transporter expression (FATP-1 in HFD and FATP-4 in STZ). Surprisingly, we observed a significantly decreased triacylglycerol content in the diaphragms of STZ-treated rats.